Strategies of Arabic Students' Self-Regulated Learning Improvement in Language Proficiency in The Disruption Era - Saproni Muhammad Samin; Ismail Akzam; Harif Supriady (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aimed to develop strategies to improve students' Self-Regulated Learning in the Arabic Language Education Study Program at Universitas Islam Riau in the Arabic language proficiency course in the disruption era. This research is qualitative research using a descriptive approach. The data collection technique for the qualitative method in this study used several designs; the Interview Technique, Documentation, and Literature Study. The systematics of strategy development refers to five stages according to Hariadi’s theory. This study shows the results of several strategies to improve Self-Regulated Learning for Arabic Language Education students at the Universitas Islam Riau for language proficiency courses; 1) Creation of environmental Arabic (Bîʾah Luġawiyyah), 2) monitoring and evaluation stages of the use of Arabic as a language of instruction lectures, 3) Coordination in the formulation of Semester Lesson Plan, 4) Orienting the religious subjects as subjects of knowledge and proficiency in the same time, 5) Motivation in competing, 6) Award Programs for student achievement, 7) Guidance lecturer in competing.